Optimal remodelling of truss structures (simulation by virtual distortions) - Kołakowski, Przemysław; Holnicki-Szulc, Jan (Computer Assisted Methods in Engineering and Science, 1997)
Optimal remodelling for least-weight trusses under single as well as multi-load state and limits imposed on local strains is considered. The so called Virtual Distortion Method is applied to simulate proces of structural remodelling through fictitious "virtual distortions" . In effect, applying knowledge of strains induced by virtual distortions modelling material redistribution, analytical formulas for sensitivity analysis and remodelling simulation process can be obtained. Various algorithms for the VDM-based structural remodelling have been proposed and tested on examples of elastic and elasto-plastic trusses.